Evaluation Of The Efficacy Of Topical Doxepin, Alone or In Combination With Topical Corticosteroid, In The Management Of Atopic Dermatitis - Dhar Sandipan; Malakar Subrata (Wolters Kluwer Medknow Publications, 1999)
In this prospective study, sixty patients, 28 male and 32 female aged 7 to 48 (mean 12.5) years, were divided into 3 equal groups. Patients in gr 1 applied 5% doxepin hydrochloride cream over the eczematous lesions twice daily for 2 weeks. Group II patients were treated with clobetasol propionate (0.05%) cream twice daily for 2 weeks. In gr III, the patients received topical clobetasol propionate twice daily for the first week and doxepin hydrochloride cream twice daily for the 2nd week. The improvement was measured by â€˜subjective sympomâ€ (SS) and â€˜objective singâ€ (OS) scoring systems. Improvement in SS was maximum in gr III moderate in gr I and mild in gr II. Improvement in OS was maximum in gr III followed by gr II and gr I. Lichenified lesions showed no improvement. Somnolence and stinging at the local site were the adverse effects complained by 8(40%) and 3(15%) patients in gr I respectively, 2(10%) patients had both in gr III.